The effects of thyme essential oil and enzyme supplementation to corn or wheat based diets on performance, carcass traits and blood metabolites in broilers - Amirahmadi, Edris; Safamehr, Alireza; Nobakht, Ali; Mehmannavaz, Yousef (Journal of the Hellenic Veterinary Medical Society, 2022)
This experiment was conducted to evaluate the effects of thyme essential oil and enzyme supplementation to corn/wheat based diets on performance, carcass traits and blood metabolites in broilers. This experiment was carried out with 432 Ross–308 broilers as factorial arrangement with 36 unites (12 birds per each replicate) in a completely randomized design from 1 up to 42 days. Result’s showed that basic ration type and meal type have statistical effects on performance (P<0.05). So that the using of wheat increased feed intake and FCR, and using soybean increased feed intake and weight gain and improved FCR (P<0.05). Meat parameters and blood parameters were not affected by the experimental treatments (P>0.05). Use of enzyme supplement or thyme essential oil in treatments containing wheat is recommended, because it can improve broilers performance parameters.